β-Carotene patch application effects on gingival crevicular fluid volume after panoramic radiography exposure - Anggun Dwi Andini; Rini Widyaningrum; Rurie Ratna Shantiningsih (Majalah Kedokteran Gigi Indonesia, 2019)
Panoramic radiography is a radiography technique which is commonly used in dentistry. X-ray radiation from panoramic radiography can cause biological damage, such as the increase of gingival crevicular fluid (GCF) volume. One of materials which was known having the ability to decrease the effect of panoramic radiography is β-carotene in mucoadhesive gingival patch form. The application of β-carotene mucoadhesive gingival patch reduce micronucleus increasing in previous study. The aim of this study is to determine the effect of β-carotene mucoadhesive gingival patch application on palatal gingiva of maxillary incisor teeth to the GCF volume of panoramic radiography exposed patients. This study involved 10 subjects (5 females and 5 males). The GCF sample was taken from the labial sulcus of 11, 12 teeth (treatment group) and 21, 22 teeth (control group) of each subject before and after panoramic radiography exposure. β-carotene mucoadhesive gingival patch was applicated on palatal gingiva before panoramic radiography examination. Sample was collected using an absorbent paper which is inserted to the labial gingival sulcus. The GCF on the absorbent papers were marked by adding ninhydrin 2%, then the GCF volume was measured using a sliding caliper. Paired t-test result shows a significant difference between GCF volume in each group before and after panoramic radiography exposure (p<0.05). Independent t-test shows no significant difference between the GCF volume difference in the control and treatment group (p>0.05). The result of this study shows that the application of β-carotene mucoadhesive gingival patch on palatal gingiva of maxillary incisor teeth shows insignificant effect in decreasing the increase of GCF volume in panoramic radiography exposed patients.